2021
DOI: 10.1002/ijop.12745
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationships among interpersonal openness trait, hostile attribution bias, and displaced aggressive behaviour: Big Five treated as covariates

Abstract: Displaced aggressive behaviour is associated with many negative outcomes. Although certain personality traits predict displaced aggressive behaviour, the uniquely longitudinal effect of indigenous interpersonal traits on displaced aggressive behaviour is ignored. To address this gap, we explored the longitudinal relationship among an indigenously interpersonal trait of China (interpersonal openness), hostile attribution bias, and self‐reported displaced aggressive behaviour. Additionally, we tested whether hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Participants responded on the 5-point scale ranging from 1 (strongly disagree) to 5 (strongly agree). After correcting the reversely scored items (one for each dimension) and averaging the score of each dimension, the final score of each personality was calculated, with higher scores indicating higher levels of the corresponding personality trait [35]. Previous research using the CBF-PI-15 has shown that it demonstrates excellent reliability and validity across diverse samples [34,36,37].…”
Section: Personality Traitsmentioning
confidence: 99%
“…Participants responded on the 5-point scale ranging from 1 (strongly disagree) to 5 (strongly agree). After correcting the reversely scored items (one for each dimension) and averaging the score of each dimension, the final score of each personality was calculated, with higher scores indicating higher levels of the corresponding personality trait [35]. Previous research using the CBF-PI-15 has shown that it demonstrates excellent reliability and validity across diverse samples [34,36,37].…”
Section: Personality Traitsmentioning
confidence: 99%
“…Displaced aggression refers to the tendency or response to harm a seemingly innocent target by a provoked person who is unwilling or unable to retaliate against the original provocateur (Denson et al, 2006; Su et al, 2021). It is a special form of reactive aggression (Su et al, 2021) because it is triggered by provocation and used to vent negative emotions such as hostility and anger.…”
Section: Introductionmentioning
confidence: 99%
“…Displaced aggression refers to the tendency or response to harm a seemingly innocent target by a provoked person who is unwilling or unable to retaliate against the original provocateur (Denson et al, 2006; Su et al, 2021). It is a special form of reactive aggression (Su et al, 2021) because it is triggered by provocation and used to vent negative emotions such as hostility and anger. The key difference from common reactive aggression is that displaced aggression targets innocent individuals, whereas reactive aggression is always directed towards the original provocateur.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations